The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1128/mcb.13.4.2469
|View full text |Cite
|
Sign up to set email alerts
|

Yeast snR30 is a small nucleolar RNA required for 18S rRNA synthesis.

Abstract: Subnuclear fractionation and coprecipitation by antibodies against the nucleolar protein NOP1 demonstrate that the essential Saccharomyces cerevisiae RNA snR30 is localized to the nucleolus. By using aminomethyl trimethyl-psoralen, snR30 can be cross-linked in vivo to 35S pre-rRNA. To determine whether snR30 has a role in rRNA processing, a conditional allele was constructed by replacing the authentic SNR30 promoter with the GALIO promoter. Repression of snR30 synthesis results in a rapid depletion of snR30 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(193 citation statements)
references
References 19 publications
3
188
1
1
Order By: Relevance
“…The bulk of the box CϩD snoRNAs are predicted to act as guides to select sites of 29-O-methylation in the pre-rRNA+ However, two box CϩD species, U3 and U14, are required for pre-rRNA processing+ Genetic depletion of U3 inhibits pre-rRNA cleavage at sites A 0 , A 1 , and A 2 ; depletion of U14 strongly inhibits cleavage at A 1 and A 2 , but has less effect on processing at site A 0 (Fig+ 1B;Li et al+, 1990;Hughes & Ares, 1991;Beltrame et al+, 1994)+ These three early cleavages are all greatly inhibited in the Nop58p depleted strain (see also Wu et al+, 1998)+ This leads to a strong impairment in the synthesis of the 18S rRNA, preventing synthesis of the small ribosomal subunits+ This inhibition most likely underlies the lethality seen on deletion of the NOP58 gene (Gautier et al+, 1997) or on genetic depletion of Nop58p+ Incorporation of [ 3 H]-uracil into newly synthesized prerRNA was strongly reduced (approximately fivefold after 6 h in minimal glucose medium), presumably because of the slowed growth rate of the Nop58p depleted cells+ Surprisingly, the incorporation of [ 3 H]-methionine into methyl groups in the pre-rRNA was reduced to the same extent+ The reduced level of pre-rRNA detected by uracil labeling is unlikely to be due to destabilization of under-methylated pre-rRNA; in strains carrying the tslethal nop1-3 mutation, methylation of the pre-rRNA was very strongly inhibited with little effect on pre-rRNA or rRNA synthesis (Tollervey et al+, 1993)+ The residual levels of the box CϩD snoRNAs present in the Nop58p depleted strain appear to be sufficient to direct the efficient methylation of the low residual levels of pre-rRNA, although it may be that a few specific sites of 29-Omethylation are more severely inhibited than is indicated by the data on bulk methylation+ In contrast, cleavage of the pre-rRNA at sites A 0 /A 1 /A 2 was strongly inhibited under the same conditions+ This indicates that higher levels of U3 and/or U14 are required to support pre-rRNA cleavage than are generally required for activity of the methylation guides+ It is notable that strains depleted of Nop1p/fibrillarin are strongly inhibited for pre-rRNA processing but have only a mild methylation defect, even though the nop1-3 allele shows strong inhibition of methylation (Tollervey et al+, 1991(Tollervey et al+, , 1993)+ One explanation would be that the pre-rRNA/snoRNA association must be sustained for longer periods of time to direct the cleavage reactions+ Binding of U14 to the pre-rRNA in the 18S rRNA region and binding of U3 to the 59 ETS region are required for the early pre-rRNA cleavages (Beltrame & Tollervey, 1992Liang & Fournier, 1995) and the time taken for these three cleavages to occur may become limiting under conditions of snoRNA depletion+ Moreover, there is likely to be a limited time window for the cleavage of sites A 0 /A 1 /A 2 + If the prerRNA is cleaved at site A 3 by RNase MRP, the resulting 23S RNA is very rapidly degraded by the exosome complex of 39 r 59 exonucleases (P+ Mitchell, E+ Petfalski, D+ Tollervey, unpubl+) preventing synthesis of the 18S rRNA+…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bulk of the box CϩD snoRNAs are predicted to act as guides to select sites of 29-O-methylation in the pre-rRNA+ However, two box CϩD species, U3 and U14, are required for pre-rRNA processing+ Genetic depletion of U3 inhibits pre-rRNA cleavage at sites A 0 , A 1 , and A 2 ; depletion of U14 strongly inhibits cleavage at A 1 and A 2 , but has less effect on processing at site A 0 (Fig+ 1B;Li et al+, 1990;Hughes & Ares, 1991;Beltrame et al+, 1994)+ These three early cleavages are all greatly inhibited in the Nop58p depleted strain (see also Wu et al+, 1998)+ This leads to a strong impairment in the synthesis of the 18S rRNA, preventing synthesis of the small ribosomal subunits+ This inhibition most likely underlies the lethality seen on deletion of the NOP58 gene (Gautier et al+, 1997) or on genetic depletion of Nop58p+ Incorporation of [ 3 H]-uracil into newly synthesized prerRNA was strongly reduced (approximately fivefold after 6 h in minimal glucose medium), presumably because of the slowed growth rate of the Nop58p depleted cells+ Surprisingly, the incorporation of [ 3 H]-methionine into methyl groups in the pre-rRNA was reduced to the same extent+ The reduced level of pre-rRNA detected by uracil labeling is unlikely to be due to destabilization of under-methylated pre-rRNA; in strains carrying the tslethal nop1-3 mutation, methylation of the pre-rRNA was very strongly inhibited with little effect on pre-rRNA or rRNA synthesis (Tollervey et al+, 1993)+ The residual levels of the box CϩD snoRNAs present in the Nop58p depleted strain appear to be sufficient to direct the efficient methylation of the low residual levels of pre-rRNA, although it may be that a few specific sites of 29-Omethylation are more severely inhibited than is indicated by the data on bulk methylation+ In contrast, cleavage of the pre-rRNA at sites A 0 /A 1 /A 2 was strongly inhibited under the same conditions+ This indicates that higher levels of U3 and/or U14 are required to support pre-rRNA cleavage than are generally required for activity of the methylation guides+ It is notable that strains depleted of Nop1p/fibrillarin are strongly inhibited for pre-rRNA processing but have only a mild methylation defect, even though the nop1-3 allele shows strong inhibition of methylation (Tollervey et al+, 1991(Tollervey et al+, , 1993)+ One explanation would be that the pre-rRNA/snoRNA association must be sustained for longer periods of time to direct the cleavage reactions+ Binding of U14 to the pre-rRNA in the 18S rRNA region and binding of U3 to the 59 ETS region are required for the early pre-rRNA cleavages (Beltrame & Tollervey, 1992Liang & Fournier, 1995) and the time taken for these three cleavages to occur may become limiting under conditions of snoRNA depletion+ Moreover, there is likely to be a limited time window for the cleavage of sites A 0 /A 1 /A 2 + If the prerRNA is cleaved at site A 3 by RNase MRP, the resulting 23S RNA is very rapidly degraded by the exosome complex of 39 r 59 exonucleases (P+ Mitchell, E+ Petfalski, D+ Tollervey, unpubl+) preventing synthesis of the 18S rRNA+…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides used for pre-rRNA hybridization were: oligo a ϭ CATGGCTTAATCTTTGAGAC, b ϭ CGGTTTTAATTGT CCTA, c ϭ TTGTTACCTCTGGGCCC, d ϭ CCAGTTAC GAAAATTCTTG, e ϭ GGCCAGCAATTTCAAGTTA, f ϭ CTCCGCTTATTGATATGC, g ϭ CCAGATAACTATCTTAA AAG, and h ϭ TTTCGCTGCGTTCTTCATC+ Oligonucleotides used for snoRNA hybridization were: oligo anti-U3 ϭ UUAUGGGACUUGUU, snR190 ϭ CGTCATGGT CGAATCGG, snR4 ϭ CACAATCCACATCGACCC, U14 ϭ TCACTCAGACATCCTAGG, U18 ϭ GTCAGATACTGTGAT AGTC, U24 ϭ TCAGAGATCTTGGTGATAAT, snR13 ϭ CA CCGTTACTGATTTGGC, snR37 ϭ GATAGTATTAACCAC TACTG, snR11 ϭ GACGAATCGTGACTCTG, snR31 ϭ GT AGAACGAATCATGACC, snR3 ϭ TCGATCTTCGTACTGTCT, snR33 ϭ GATTGTCCACACACTTCT, snR36 ϭ CATCCAGC TCAAGATCG, snR42 ϭ CTCCCTAAAGCATCACAA, and MRP ϭAATAGAGGTACCAGGTCAAGAAGC+ Antisense transcripts specific to snR30 and snR10 were made from vectors pT3/T7-snR30 (Morrissey & Tollervey, 1993) and pT3/ T7-snR10 following appropriate linearization+ To detect the NOP58 mRNA, a fragment spanning the whole ORF of NOP58 was generated by PCR and labeled using the Prime-a-Gene Labeling kit (Promega)+…”
Section: Immunoprecipitation Of Prota-nop58p and Prota-nop58pdkkementioning
confidence: 99%
See 1 more Smart Citation
“…The nucleolus compartment of eukaryotic cells is devoted to the assembly of large and small ribosomal subunits (reviewed by Mélèse & Xue, 1995)+ The association of almost 80 ribosomal proteins into 60S and 40S subunits occurs concomitantly with the maturation of ribosomal RNA (rRNA) molecules+ The rRNAs have a mixed transcriptional origin+ The nucleolar RNA polymerase I transcribes a single, large rRNA precursor 35S which is processed into three mature rRNAs (18S, 5+8S and 25S)+ The fourth eukaryotic rRNA molecule (5S) is transcribed independently by RNA polymerase III+ The 5S, 5+8S and 25S rRNA species constitute the RNA molecules of mature 60S subunits whereas mature 40S subunits contain only 18S rRNA+ The maturation of the pre-rRNA 35S polymerase I transcript is largely studied in yeast and numerous small nucleolar RNAs (snoRNAs) and protein components involved in this process have been characterized (Eichler & Craig, 1994;Venema & Tollervey, 1995;Tollervey & Kiss, 1997)+ The 35S primary transcript is successively matured by both endonucleolytic and exonucleolytic cleavages that generate stable rRNA precursors whose identification by in vivo labeling or by Northern hybridization has led to the processing pattern drawn in Figure 1+ The nucleic cleavages contribute to a precise excision of both external (59 and 39 ETS) and internal transcribed spacers (ITS1 and ITS2) that interrupt the 35S rRNA sequence+ Aberrations in any of the cleavage steps result in a defective maturation that modifies the reference pattern shown in Figure 1+ In such cases, an increase or decrease in intermediate precursors is evident whereas some aberrant and sometimes deadend pre-rRNA species are detected+ This observation of altered profiles is classically used to determine at which step either a given mutation or the depletion of a cellular component will affect the rRNA maturation process+ These approaches have indeed revealed that a large number of trans-acting factors are required for the same processing step (Venema & Tollervey, 1995)+ For example, the snoRNAs U3, U14, snR30, and snR10 are all essential (or at least important in the case of snR10) for efficient cleavage at sites A 0 , A 1 , and A 2 (Tollervey, 1987;Li et al+, 1990;Hughes & Ares, 1991;Morrissey & Tollervey, 1993; see Fig+ 1B)+ The snoRNAs are believed to function as small nucleolar ribonucleoprotein (snoRNP) complexes rather than as free RNAs (Maxwell & Fournier, 1995) and some nucleolar proteins were shown to be physically associated with snoRNAs (Maxwell & Fournier, 1995;Smith & Steitz, 1997)+ Two RNP particles involved in the yeast rRNA processing are considered in this article: the abovementioned snoRNP complex (Venema & Tollervey, 1995) and the RNase MRP complex …”
Section: Introductionmentioning
confidence: 99%
“…Nuclei of eukaryotic cells contain a large number of small nucleolar RNAs (snoRNAs) that actively participate in ribosome biogenesis+ All of them, with the exception of MRP RNA (Maxwell & Fournier, 1995;Tollervey & Kiss, 1997), can be grouped into two major families that are structurally and functionally distinct: the box C/D and the box H/ACA snoRNAs+ Although some snoRNAs belonging to both classes are required for cleavage of pre-rRNA (box C/D: U3, U8, U14, U22; box H/ACA: snR30, U17, E2, E3; Hughes & Ares, 1991;Morissey & Tollervey 1993;Maxwell & Fournier, 1995;Enright et al+, 1996;Borovjagin & Gerbi, 1999), most of them function as guides in posttranscriptional modification of pre-rRNA+ The box C/D snoRNAs direct the site-specific 29-O-methylation of pre-rRNA (Cavaillé et al+, 1996;Kiss-László et al+, 1996;Maden, 1996;Nicoloso et al+, 1996;Tollervey, 1996;Tycowski et al+, 1996;Bachellerie & Cavaillé, 1997;Maden & Hughes, 1997;Kiss-László et al+, 1998), whereas the box H/ACA snoRNAs are involved in site-specific conversion of uridines into pseudouridines (Balakin et al+, 1996;Ganot et al+, 1997)+ A stem-loop structure has been proposed for the members of box C/D snoRNA family (Bachellerie et al+, 1995); this model predicts that the 59 and 39 termini of the snoRNA form a short terminal stem (at least 4 bp) that delimitates a loop region where two highly conserved sequence elements (boxes C and D) are localized+ The boxes are positioned on opposite sides of the loop and are brought in close proximity by the terminal stem+ In many cases an internal stem can further stabilize this structure (Tycowski et al+, 1993;Nicoloso et al+, 1994)+ In intron-encoded snoRNAs, where a canonical terminal stem is absent, external intronic complementary sequences have been shown to perform the function of juxtaposing the boxes C and D (T+ Villa, pers+ comm+)+ Extensive mutagenesis analysis carried out on mouse U14 snoRNA (Xia et al+, 1997) has led to the definition of a "minimal core motif" including the conserved boxes and the terminal stem+ This motif is essential for the biosynthesis (Caffarelli et al+, 1996;Watkins et al+, 1996;Xia et al+, 1997), the metabolic stability …”
Section: Introductionmentioning
confidence: 99%